2000
DOI: 10.1093/humrep/15.7.1640
|View full text |Cite
|
Sign up to set email alerts
|

Serum inhibin A and activin A are elevated prior to the onset of pre-eclampsia

Abstract: Serum inhibin A and activin A concentrations increase in pre-eclampsia. We investigated the time courses of the changes in relation to the onset of the maternal syndrome and if their measurement could be useful for clinical prediction particularly in relation to early onset disease, the most severe of the clinical presentations. Serial samples were taken from 1496 healthy nulliparae. Changes in activin A and inhibin A were analysed in women with: early onset pre-eclampsia (n = 11), pre-eclampsia delivering at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(87 citation statements)
references
References 31 publications
7
75
1
4
Order By: Relevance
“…Activin A seems to be a sensitive marker for the risk of later development of preeclampsia at 21-25 wk of gestation [70] . Inhibin A is thought to be more sensitive than activin A in predicting cases of early-onset preeclampsia at 15-19 wk of gestation [70] . P-selectin P-selectin belongs to the group of cell adhesion molecules.…”
Section: Placental Protein 13mentioning
confidence: 99%
“…Activin A seems to be a sensitive marker for the risk of later development of preeclampsia at 21-25 wk of gestation [70] . Inhibin A is thought to be more sensitive than activin A in predicting cases of early-onset preeclampsia at 15-19 wk of gestation [70] . P-selectin P-selectin belongs to the group of cell adhesion molecules.…”
Section: Placental Protein 13mentioning
confidence: 99%
“…In contrast, Silver et al [6] also examined women with PE, GH and normotensive controls and reported that the median value was 1.0 MoM in controls, 2.0 MoM in GH and 3.0 MoM in PE. Muttukrishna et al [43] measured serum activin A longitudinally during pregnancy and reported that during the third trimester the levels were significantly increased in both those developing PE and GH, but in the second trimester increased levels were observed only in the PE group. The possibility of different mechanisms underlying the increased serum activin A concentration in PE and GH was raised by a study investigating the effect of treating hypertension in such patients by ␣ -methyldopa [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Muttukrishna et al [43] reported that at 21-25 weeks serum activin A was above the 90th and 95th percentiles in 59 and 38%, respectively, of cases that subsequently developed PE. Florio et al [16] estimated that screening for PE by activin A at 24 weeks would have a detection rate of 61% at a false positive rate of 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Muttukrishna et al found that maternal serum concentrations of inhibin A and activin A are more elevated in women with preeclampsia as compared to normotensive control women [23]. Some authors have confirmed that elevated inhibin A/activin A levels in first trimester [24,25] or in second trimester [26][27][28][29][30] could predict preeclampsia (Table II). Spence et al found that elevated inhibin A and activin A levels combined with uterine artery doppler measurement become a more accurate predictive values in second trimester [30].…”
Section: Inhibin a And Activin Amentioning
confidence: 96%